2017
DOI: 10.1016/j.vaccine.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to human papillomavirus vaccination and natural exposure in individuals with Fanconi Anemia

Abstract: Fanconi anemia (FA) is a rare genetic disorder associated with predisposition to head and neck and gynecological squamous cell cancers. In the general population, these cancers are commonly linked to human papillomavirus (HPV) infection. Antibodies to natural HPV infection and HPV vaccination were evaluated in 63 individuals with FA while considering host immune factors. Approximately 30% of reportedly unvaccinated participants were seropositive (HPV6–38%, HPV11–25%, HPV16–26%, and HPV18–26%). Seropositivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…There were no statistically significant differences between the median time of sampling for this study and time post HPV vaccination for non-transplanted (median = 3 years; range 2–6 years) and transplanted groups (median 3 years; range 1-6 years) ( p = 0.27). Non-transplanted participants with FA had higher GMTs than the transplanted FA group regardless of vaccination status consistent with our previous findings [ 26 ] ( Table 7 ). Significant differences were observed with HPV18, 31 and 58.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…There were no statistically significant differences between the median time of sampling for this study and time post HPV vaccination for non-transplanted (median = 3 years; range 2–6 years) and transplanted groups (median 3 years; range 1-6 years) ( p = 0.27). Non-transplanted participants with FA had higher GMTs than the transplanted FA group regardless of vaccination status consistent with our previous findings [ 26 ] ( Table 7 ). Significant differences were observed with HPV18, 31 and 58.…”
Section: Resultssupporting
confidence: 91%
“…Blood samples were collected using appropriate precautions by trained personnel. Fifty percent of the samples from participants with FA were collected at Cincinnati Children’s Hospital, with the remainder collected at FARF events as previously described [ 26 ]. Eighty-three percent of healthy control samples were collected at Cincinnati Children’s Hospital with the remainder collected from spouses and friends who attended FARF events with those with FA.…”
Section: Methodsmentioning
confidence: 99%
“…These works support the hypothesis that the damage in the FA pathway may help the development of HPV‐associated cancers in individuals with FA. Although OSCC in patients with FA does not seem to be caused by HPV infection, patients with FA should consider vaccination to prevent HPV‐associated cancers …”
Section: Risk Factors and Prevention Of Oscc In Famentioning
confidence: 99%
“…Although OSCC in patients with FA does not seem to be caused by HPV infection, patients with FA should consider vaccination to prevent HPV-associated cancers. 3,88,97 Patients with FA can present potentially malignant disorders, especially oral leukoplakia (Fig. 2), 98,99 defined by the World Health Organization as "a white patch or plaque that cannot be characterized, clinically, or pathologically as any other disease."…”
Section: Risk Factors and Prevention Of Oscc In Famentioning
confidence: 99%
“…Seropositivity ranged from 7 to 21% for skin HPV types and from 7 to 38% for mucosal HPV types in unvaccinated individuals with FA; in self-reported vaccine recipients, the serological positivity to HPV vaccine types was 75 to 96% [ 76 ]. Our more recently published study of the immune response in FA reported antibody responses to natural HPV infection and HPV vaccination in 39 unvaccinated and 24 vaccinated patients for HPV [ 77 ]. Similar to the earlier study, 30% of reportedly unvaccinated individuals were seropositive.…”
Section: Response To Hpv Vaccine In Individuals With Famentioning
confidence: 99%